The Role of Technology in Pluralism and Multicultural Learning During the Pandemic Era for Islamic Elementary School Students. - Mukhlisoh, Mukhlisoh (PT. Anagata Sembagi Education, 2025)
The purpose of the study was to investigate the role of pluralism and multicultural learning in the pandemic era for students of Madrasah Ibtidaiyah (MI) in Cirebon Regency, West Java. The research method used is qualitative-descriptive with data collection techniques from observations, interviews, and documentation studies that focus on the themes of pluralism education, multicultural education, and online learning for MI students. The findings reveal that the practice of learning pluralism and multiculturalism in the pandemic era is carried out by integrated Islamic and social studies teachers. Learning practices are carried out with special characteristics that are different from elementary schools, namely online learning guided by Islamic values ​​(Al Quran and Hadith). The values ​​taught are not about tolerance (tasamuh), mutual cooperation, and respect for others where the concepts of pluralism and multiculturalism are packaged in such a way that students can understand them from a religious point of view. The conclusion is that pluralism and multicultural education during the pandemic is very dependent on technology such as online learning models and learning applications. The selection of the right learning method refers to the theory of technology-based learning that can support pluralism and multicultural learning. In addition, it is very important to understand the 2022 curriculum so that learning in the new school year can quickly adapt to the pandemic situation and the students themselves. The results of this study serve as input for educational institutions, especially teachers in relevant fields of science to improve learning models in supporting educational goals in Indonesia